The UK and social security coordination after Brexit: reinventing the wheel or Mad Hatter's tea party - Roberts, Simon (University of Warsaw, 2017)
On 23 June 2016 the United Kingdom voted in a referendum to leave the European Union. On 17 January 2017, the UK Prime Minister, Theresa May, stated that what she is seeking is “Not partial membership of the European Union, associate membership of the European Union, or anything that leaves us half-in, half-out. We do not seek to adopt a model already enjoyed by other countries. We do not seek to hold on to bits of membership as we leave. No, the United Kingdom is leaving the European Union” (Reuters, 16 January 2017). It is by no means clear what “leaving” the EU will mean for the UK, the EU and the millions of European citizens who have exercised their right to free movement enshrined in the Treaty of Rome “with the legitimate expectation that their EU citizenship rights were irrevocable.” (UK Citizens in Europe, “Towards an Alternative White Paper on the European Union (Notififi cation of Withdrawal) Bill”, February, 2017). This article considers the implications of the UK’s decision to leave the EU for mobile EU citizens’ social security and healthcare rights in the UK and UK nationals’ corresponding rights in the EU. It examines the rights at stake and possible arrangements to coordinate social security following Brexit. The article concludes that the most effective arrangement would look conspicuously similar to the current coordinating Regulations 883/04 and 987/09. However, in the event of a ‘Hard’ Brexit new institutional arrangements would have to be found to administer, review, revise, interpret, and provide consistency and legal certainty across at least 30 countries.